Comparison of Fear of Falling Experienced by the Elderly Who Live in Urban and Rural Areas - Ulfiana, Elida; Makhfudli, Makhfudli; Haryanto, Joni; Chotimah, Kusnul (International Journal of Psychosocial Rehabilitation, 2020)
Fear of Falling (FOF) is a risk factor for falls in the elderly. The fear of falling on the elderly often leads to undesirable health effects such as limitation of activity, falls, depression, social isolation, and reduced quality of life. Falling in the elderly is a serious problem in society including those living in urban and rural areas. The purpose of this study is to compare the fear of falls experienced by the elderly who live in urban and rural areas. This research method was a comparative study, using simple random sampling with a sample of 210 elderly consisting of 108 elderly living in urban cities of Surabaya and 102 rural elders in Lamongan Regency, East Java Province, Indonesia. The questionnaire used was FES-I with analysis using Mean-Whitney test. The results showed that for FOF in the elderly in urban areas 34% were in the low category, 52% had a moderate fear, and 14% had a high fear. Whereas, for elderly in rural areas FOF for 58% was high, 22% had a moderate fear, and 21% low. There were differences in fear of falling between the elderly in urban and rural groups with a value of p < 0.05. Conclusion: the elderly who live in rural areas have more fear of falling than the elderly in urban areas related to the safety of the home environment.